ANALISIS PERSEPSI HAK INDIKASI GEOGRAFIS SALAK PONDOH PADA KOMUNITAS AGROWISATA DI KABUPATEN SLEMAN - susilo budi winarno; Tuti Panghastuti (Journal of Tourism Destination and Attraction, 2020)
Geographical Indication of Agro-tourism is a unique tourism activity to areas or rural locations whose products are already known to have superior quality and characteristics. "Salak Pondoh Sleman Jogja" fruit is a product of natural resources that has the rights of Geographical Indication Rights exclusively. This research aims to know the perception and understanding of Geographical Indication Rights for future planning of the development of Sleman Salak Pondoh agro-tourism based on Geographical Indication Rights. The population in this study were communities related to geographical indications on the Salak Pondoh Sleman. The sample in this study is a non-random sampling method with sample subjects are: Komunitas Perlindungan Indikasi Geografis Salak Pondoh Sleman (KPIG-SPS) community. Primary data used in this research were collected directly in the field through field research, and secondary data collected from the literature study.